Novel Method of Graphite Exfoliation. Issue 19 (14th March 2016) - Novikau, Uladzimir; Razanau, Ihar; Filipovich, Sviatlana
ABSTRACT: The paper describes a novel method of exfoliated graphite synthesis. The method includes synthesis of graphite intercalation compound in liquid ammonia medium and subsequent intercalate decomposition with graphite exfoliation. Influence of the experimental parameters on the morphology and structure of the exfoliated graphite is shown. Comparison of the developed exfoliation method to the high-temperature oxidation-reduction method used in industrial scale nowadays is presented. A number of application areas for the synthesized exfoliated graphite are described.